Fertilização Organomineral no milho em condições de Cerrado - Silva, Renan Cesar Dias da (2020)
The use of organomineral fertilizer can improve the absorption efficiency of nutrient , mainly of phosphorus and nitrogen and, therefore, reduce the costs with fertilizer application, in addition to improving the physical-chemical quality of the cultivated soils. This study aimed to evaluate the effects of organomineral fertilizer on the supply of phosphorus and nitrogen compared to mineral in two different soil textures, in corn crop. Two trials were conducted in the city of Uberlândia-MG, in an area with a clayey and sandy soil texture. In the experiment to evaluate the organomineral in the phosphorus supply , the experimental design was in randomized blocks, with five replications, being five doses of the organomineral fertilizer: 40, 60, 80, 100 and 120% of the recommended dose of P2O5 for corn and an additional treatment with 100% of the recommendation of P2O5 using mineral source. Thus, six treatments and 30 plots were totaled. The fertilization recommendation was for productivity above 8,000 kg ha-1 of grains, being 120 kg kg ha-1 and 80 kg ha-1 of P2O5 in sandy and clayey soils, respectively. In the organomineral experiment in nitrogen supply , the design was in a factorial scheme 2 x 5 + 2 in randomized blocks with four replications, being two times of application , five doses of pelleted nitrogen organomineral fertilizer (40, 60, 80, 100 and 120% of the recommended nitrogen dose for the corn) and two additional treatments with 50% and 100% of the nitrogen recommendation using mineral source. The results of the application of phosphated orgamineral showed that, with the exceptions of the leaf content of phosphorus and productivity in the sandy texture and the number of grains per row, in the clay texture, there was no difference between the doses of phosphate organomineral as they did not differ from the additional mineral. These results indicate that phosphate organomineral is as efficient as mineral phosphorus. Regarding the time of application , in the experiment with nitrogen fertilization, the installment of the application in V2 (50%) + V4 (50%) presented the best increments for stem and ear diameter, ear length and number of grains per row. Thus, it is concluded that, with the exceptions of the leaf content of nitrogen, potassium and dry mass in the soil of sandy texture and the diameter of cob in the soil of clay texture , there was no statistical difference between the doses of nitrogenous organomineral as they did not differ from the additional mineral . In this way, the nitrogenous organomineral fertilizer is as efficient in maize culture as the source of mineral nitrogen.